2010
DOI: 10.1016/j.cell.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Signaling in Osteoblasts Integrates Bone Remodeling and Energy Metabolism

Abstract: The broad expression of the insulin receptor suggests that the spectrum of insulin function has not been fully described. A cell type expressing this receptor is the osteoblast, a bone-specific cell favoring glucose metabolism through a hormone, osteocalcin, that becomes active once uncarboxylated. We show here that insulin signaling in osteoblasts is necessary for whole-body glucose homeostasis because it increases osteocalcin activity. To achieve this function insulin signaling in osteoblasts takes advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
1,065
8
33

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 998 publications
(1,142 citation statements)
references
References 48 publications
36
1,065
8
33
Order By: Relevance
“…We found that the answers to these two questions were tightly linked. (3,8) The insulin receptor is receptor tyrosine kinase (RTK), and a classic mechanism to downregulate the activities of RTKs is through the action of an intracellular tyrosine phosphatase. Indeed, insulin signaling in myoblasts and hepatocytes is negatively regulated by a protein tyrosine phosphatase called PTP-1B.…”
Section: Novel Findings Novel Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the answers to these two questions were tightly linked. (3,8) The insulin receptor is receptor tyrosine kinase (RTK), and a classic mechanism to downregulate the activities of RTKs is through the action of an intracellular tyrosine phosphatase. Indeed, insulin signaling in myoblasts and hepatocytes is negatively regulated by a protein tyrosine phosphatase called PTP-1B.…”
Section: Novel Findings Novel Questionsmentioning
confidence: 99%
“…This hypothesis turned out to be correct. One of us (GK) showed that osteoblasts secrete osteocalcin, (3) one of the most abundant proteins of the bone extracellular matrix. (4) Osteocalcin is made only by osteoblasts and is subject to posttranslational carboxylation on three or four glutamic residues, depending on the species, that provides the molecule high affinity for hydroxyappatite.…”
Section: Introductionmentioning
confidence: 99%
“…(48,49) Thus, in osteoblasts, insulin signaling regulates expression of Runx2 and production of osteocalcin. In addition, insulin increases support for osteoclastogenesis by decreasing expression of osteoprotegerin (OPG), a decoy receptor for RANKL.…”
Section: Skeletal Control Of Metabolic Balancementioning
confidence: 99%
“…The genetic absence of Esp1 in mice results in significant hypoglycemia, due to excess undercarboxylated osteocalcin. (48,51) On the other hand, FoxO1 upregulates Esp1 expression, thereby impairing glucose tolerance. (52) Thus, in mice there is a complex interaction between glucose homeostasis and skeletal remodeling.…”
mentioning
confidence: 99%
“…The osteoblast is thought to be the main actor, affecting multiple organs, such as the BM, the pancreas, and the testis. It regulates hematopoiesis directly as a hematopoietic stem cell (HSC) niche (1,2), as well as energy metabolism and male fertility by producing osteocalcin (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%